BUILDING A FUTURE-READY WORKFORCE: HR'S ROLE IN STRATEGIC TALENT PLANNING - Asniati; Dhenny Asmarazisa; Catur Fatchu Ukhriyawati (RADJA PUBLIKA, 2025)
In an era defined by technological disruption, shifting demographics, and economic volatility, building a future-ready workforce is a paramount strategic challenge. This article argues that the Human Resources function must fundamentally evolve from an administrative supporter to a strategic partner to lead this imperative. Through a qualitative multi-case study methodology, the research explores how leading organizations leverage data-driven talent planning, a skills-based approach, and a culture of continuous learning to foster organizational agility. The findings present a framework for strategic talent planning, identifying key enablers such as a strong CEO-CHRO partnership, integrated technology, and a growth mindset culture, while also acknowledging barriers like organizational silos and legacy systems. The study concludes that HR's ability to interpret human capital data and align talent strategy with long-term business goals is not merely beneficial but essential for securing sustainable competitive advantage and ensuring organizational resilience in the face of constant change.